One-eye-set sugarcane susceptibility to weed interference - Beluci, Lucas R. [UNESP]; Bacha, Allan Lopes [UNESP]; Barroso, Arthur A. M.; Alves, Pedro Luis C. A. [UNESP] (FapUNIFESP (SciELO), 2018)
The new technology of sugarcane planting, known as one-eye-set seedlings, offer a high standard of plant health and vegetative vigor. However, there are no reports in the literature that evaluate the weed competition with one-eye-set sugarcane seedlings, and the periods in which weed communities need to be controlled in this system. Two interference experiments were conducted in field conditions. The first experiment determined the periods of weed interference of an infesting community predominated by Ipomoea hederifolia and Merremia aegyptia in sugarcane. In the second experiment, these same species competed with plants of the same sugarcane cultivar. Productivity and qualitative aspects of production were evaluated. The critical period of interference prevention in one-eye-set sugarcane system was 103 days, with weed community interference starting at 35 days and lasting until 138 days after planting. Weed coexistence during the entire sugarcane cycle reduced productivity by 60% and affected qualitative characteristics such as the total reducing sugars. Both species affected the vegetative development of the crop, mainly the tillering. I. hederifolia plants developed ahead of the M. aegyptia plants but in late evaluations the interference caused by M. aegyptia (77%) was greater (P<0.01) than that caused by I. hederifolia (72%).
Keywords: Competition; Critical period of interference prevention; Morning glory species; Periods of interference; Sugarcane OES